Formacja kandydatów do kapłaństwa w świetle nowego Ratio fundamentalis institutionis sacerdotalis - Selejdak, Ryszard (Collectanea Theologica, 2018)
The last Ratio Fundamentalis Institutionis Sacerdotalis was published in 1970 and updated in 1985. In the meantime, and particularly under the effect of the rapid changes in the modern world, the historical, socio-cultural and ecclesial contexts have changed, in which the priest is called to make manifest the mission of Christ and the Church. This has also led to significant changes in related matters: the image or the view of the priest, the spiritual needs of the People of God, the challenges of the new evangelisation, and the languages of communication, to name just a few. In this situation, it seemed that priestly formation needed to be relaunched, renewed and returned to the centre. On 8 December 2016, therefore, the Congregation for the Clergy published the new Ratio Fundamentalis Institutionis Sacerdotalis, a tool for the formation of priests. It has taken up the contents, methods and approaches presented so far in the field of formation, updating them and introducing new elements. The document restates the guidelines offered in the Apostolic Exhortation Pastores Dabo Vobis regarding an integrated formation of seminarians. In this formation, the formators and professors are called to demonstrate the close relationship between theology, the spiritual life and the pastoral ministry. This is so in order that the candidate for the priesthood might become a good shepherd of the People of God and have a compassionate and merciful heart like Christ.